Electricity Price and Demand Pattern Changes Due to Increases in Solar Generation in German Electricity Markets - Smolen, Jan; Dudic, Branislav (International Journal of Energy Economics and Policy, 2018)
This article aims to explain the impacts of increases in solar generation in Germany on intra-day electricity price and demand patterns during the last decade. Electricity demand sensitivity to the changes in price patterns is also analyzed. It is concluded that there is a clear relationship between the amount of solar generation and daily peak price premiums over the average daily price. With increased solar generation, peak hour electricity price premiums are gradually decreasing. This relation is even more visible during the summer months, with higher amount of solar power produced. However, demand response analysis to the changes in price patterns has provided less conclusive results. While, between years 2007 and 2013, demand clearly adjusted relatively higher, with relatively lower peak prices, more recent periods haven't fully confirmed this trend. Some theories explaining the possible reasons for this fact are also presented in the article. Keywords: Electricity Price, Renewable Generation, Demand Response JEL Classifications: Q41, Q42 DOI: https://doi.org/10.32479/ijeep.7067